Do People Determine Their Subjective Socioeconomic Status Based on the Housing Type and Residential Neighborhood? Empirical Evidence from Seoul - Su Jin Kang; Wonseok Seo (Land, 2022)
Housing has traditionally been regarded as the most valuable asset in South Korea and is frequently used as an indicator of an individual’s socioeconomic status. In particular, this preference is evolving into a classification criterion for social class. This has led to rising social conflict and social anxiety in recent years. In this regard, this study examined the effect of residential characteristics, namely housing type and residential neighborhood, on subjective socioeconomic status using a multi-level logistic model centered on Seoul. The following are the key findings: First, it is demonstrated that home ownership has a substantial effect on subjective socioeconomic status. Second, the subjective socioeconomic status was found to vary depending on the type of housing in which a person currently resides, with residents of single-family housing having a higher subjective socioeconomic status than residents of other housing types. Third, residents of multi-household housing evaluated their socioeconomic status as the lowest. Fourth, the type of housing in one’s residential neighborhood was also found to be a significant factor in determining subjective socioeconomic status. Fifth, complex residential characteristics, such as the type of housing in which a person currently resides and the type of housing in the residential neighborhood, were found to have a considerable effect on subjective socioeconomic status. Through empirical analysis, this study examined the implications of inclusive housing policies that can reduce social problems and class conflicts and clearly identified the impact of residential characteristics on subjective socioeconomic status.